2010
DOI: 10.3748/wjg.v16.i23.2901
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein in paediatric inflammatory bowel disease

Abstract: The measurement of hs-CRP did not prove useful in the assessment of disease activity or glucocorticoid treatment in paediatric IBD patients that had undetectable standard CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 30 publications
0
19
0
2
Order By: Relevance
“…With an arbitrary cut-off value of 1 mg/dl, there was a 73% sensitivity and 91% specificity in the prediction of granulomatous CD (OR 28; 6-134.32; p < 0.00001). A Finish study [37] reached comparable conclusions, and it was speculated that higher local production of TNF-a in the granulomatous lesions of CD patients could explain higher CRP levels.…”
Section: Crp Levels and CD Phenotypementioning
confidence: 83%
See 3 more Smart Citations
“…With an arbitrary cut-off value of 1 mg/dl, there was a 73% sensitivity and 91% specificity in the prediction of granulomatous CD (OR 28; 6-134.32; p < 0.00001). A Finish study [37] reached comparable conclusions, and it was speculated that higher local production of TNF-a in the granulomatous lesions of CD patients could explain higher CRP levels.…”
Section: Crp Levels and CD Phenotypementioning
confidence: 83%
“…Earlier studies already demonstrated the importance of CRP measurement as a guide in the determination of extent and in the management of patients with attacks of UC [34,35]. Yet, most of studies concluded that CRP levels in UC were lower than that in CD [24][25][26]29,31,[36][37][38]. There was also a bigger percentage of patients with normal CRP in UC than in CD.…”
Section: Versus Ucmentioning
confidence: 89%
See 2 more Smart Citations
“…30 It is noteworthy that a recent Finnish study found no incremental benefit from the use of high-sensitivity CRP over that of standard CRP in children. 31 It is important to note that the tightness and even the direction of these correlations may vary when a given marker is used to study patients with either UC or CD, when evaluating patients with mucosal inflammation in different anatomic locations and even when different types of treatment are used. For example, several studies have suggested a trend for closer correlation between clinical activity and CRP in patients with CD and with ESR in those with UC.…”
Section: Clinical Activity Indicesmentioning
confidence: 99%